Designing international environmental agreements : incentive compatible strategies for cost-effective cooperation - Schmidt, Carsten (Cheltenham, UK ; Northampton, Mass : Edward Elgar, 2000)
This study combines two core dimensions of international environmental policy: the traditional search for cost-effective policy instruments and the creation of incentives for voluntary cooperation among sovereign nations. the analysis offers some clear-cut policy recommendations for the design of environmental treaties and for the further development of existing international institutions to protect the global environment.
Includes bibliographical references 9p. 201-217) and index.
nmn,08/08/16
Loan
Keywords: Environmental economics; Environmental policy; Environmental policy